A Systematic Derivation of Stochastic Taylor Methods for Stochastic Delay Differential Equations - Rosli, Norhayati; Bahar, Arifah; Yeak, S H; Mao, X (Bulletin of the Malaysian Mathematical Sciences Society, 2013)
This article demonstrates a systematic derivation of stochastic Taylor methods for solving stochastic delay differential equations (SDDEs) with a constant time lag, ... The derivation of stochastic Taylor expansion for SDDEs is presented. We provide the convergence proof of one--step methods when the drift and diffusion functions are Taylor expansion. It is shown that the approximation solutions for SDDEs converge in the ...-norm. 2010 Mathematics Subject Classification: 65C99 (ProQuest: ... denotes formulae omitted.)